Non-Pharmacological Treatments for Stuttering in Children and Adults: A Systematic Review and Evaluation of Effectiveness, and Exploration of Barriers to Successful. (30th June 2015) - Baxter, S.; Johnson, M.; Cantrell, A.; Blank, L.; Brumfitt, S.; Enderby, P.; Goyder, E.
Abstract: There is an increasing range of treatments available for stuttering in children and adults and a need to examine the evidence base for these interventions in order to inform future guidelines and service delivery. Systematic reviews provide a structured summary of available evidence and can identify consistencies and inconsistencies in the research in order to present service providers and practitioners with evidence-based information. The systematic review that will be reported in this presentation was commissioned by the National Institute for Health Research as part of its Health Technology Appraisal programme, and is being carried out over one year (August 2013-August 2014). The systematic review consists of two elements: a synthesis of international evidence on the effectiveness of stuttering interventions; and an examination of qualitative primary study data for insights into factors that may underpin successful or less successful outcomes. A systematic search of key health and medical databases is being undertaken to identify recently published (since 1990) relevant studies. In addition to electronic searching, reference list checking, involvement of experts and citation searching is being used to identify evidence. The review process includes quality appraisal of each study to identify potential sources of bias and reliability of findings. Following the identification and quality appraisal, included studies will be synthesised (via appropriate methods including narrative synthesis, meta-analysis and thematic synthesis). The review is intending to be a broad review of the evidence regarding stuttering intervention. Populations of children, adolescents and adults who have developmental dysfluency in any OECD country are included. Non-pharmacological interventions delivered in any setting, by any individual are eligible for inclusion. Any outcome relating to a positive effect on stuttering or the emotional wellbeing of people who stutter is considered. A broad study design criteria has been set, with only case series, case reports and survey data excluded. The study is currently ongoing and will be completed in August 2014. To date we have examined over 4000 retrieved citations and identified 120 intervention studies and 24 qualitative studies for potential inclusion. A conceptual framework outlining the pathway from interventions to outcomes is being developed from the literature to provide further explanatory detail of the review findings. The presentation will consider the implications of the findings of the systematic review for practitioners and commissioners.